A Deactivation Correlation for Platinum Y-Zeolite in n-Hexane Isomerization - Haiyam Mohammed A. Al-Raheem (Engineering and Technology Journal, 2011)
The objective of the present work is to realize the kinetic modeling regarding deactivation of Pt-HY zeolite and monitor the isomerization reaction of n-hexane. The catalyst has been prepared with o.4% Pt and evaluated during the isomerization reaction of n-hexane. Based on the results of catalytic investigation, a kinetic model was proposed to deactivate the catalyst by coke formation. The present method provides information on apparent overall kinetics as well as deactivation parameters and would seem to provide a rapid method for screening of reaction/deactivation behavior. Accordingly the deactivation order was found to be 3.72. The obtained correlation of deactivation predicts the activity pattern under the applied reaction conditions, closely mimics those observed experimentally, and spans those obtained from empirical correlations.